1995
DOI: 10.1177/089686089501500104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Straight and Curled Tenckhoff Peritoneal Dialysis Catheters Implanted by Percutaneous Technique: A Prospective Randomized Study

Abstract: Objective To examine the impact of peritoneal dialysis catheter configuration, curled or straight catheter, on catheter survival and mechanical and infectious complications. Design Prospective randomized trial. Setting Department of Nephrology of a single university hospital. Patients Seventy-two consecutive patients initiating peritoneal dialysis were randomized to receive either a single cuff straight catheter or a single cuff curled catheter, implanted by percutaneous technique. Results Significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
69
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 9 publications
4
69
0
2
Order By: Relevance
“…Cuff extrusion was strongly associated with the presence of ESI. Also, in agreement with previous studies (29), the straight catheters compared with coiled ones displayed a fourfold and sevenfold higher risk for outflow failure and migration, respectively. Therefore we consider PDC configuration as the most important factor for tip migration and outflow failure.…”
Section: Discussionsupporting
confidence: 92%
“…Cuff extrusion was strongly associated with the presence of ESI. Also, in agreement with previous studies (29), the straight catheters compared with coiled ones displayed a fourfold and sevenfold higher risk for outflow failure and migration, respectively. Therefore we consider PDC configuration as the most important factor for tip migration and outflow failure.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that a well-planned and implemented technique may avoid the need for direct or The total incidence of peritonitis episodes was one every 29.5 months (0.44 episodes/patient-year) and no significant difference was verified regarding this complication among the groups. These results were very similar to those reported in the literature for percutaneous and surgical catheter placements (22,(26)(27)(28)31,32,34). On the other hand, there are few publications on image-guided procedures, with some reports describing an incidence of one episode of peritonitis every 14.5-21.1 months (33)(34)(35).…”
Section: Discussionsupporting
confidence: 87%
“…Concerning the incidence of dialysate leakage, there are even more conflicting results in the literature. In percutaneous insertions, not guided by radioscopy, it has been reported that the incidence of this complication can be higher than 20-30% (26)(27)(28)(29). On the other hand, with regard to surgical technique, this specific complication is apparently less common ranging from 0.9 to 15.3% (31,34).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6,7 Although different types of PD catheter such as tenckhoff straight, swan-neck and tenckhoff coiled catheter have been designed and used, there's no consensus on which type of catheter is better. [8][9][10] The ideal type of catheter may depend on the operative insertion technique. 11 Thus, in this study, we developed a new open laparotomy surgery technique with catheter fixation to the lower abdominal wall combined with a straight upward tunnel, a low implant position and a shorter intra-abdominal catheter section.…”
Section: Discussionmentioning
confidence: 99%